2019
DOI: 10.1146/annurev-cancerbio-030518-055905
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ Metabolism in Aging and Cancer

Abstract: Aging is a major risk factor for many types of cancer, and the molecular mechanisms implicated in aging, progeria syndromes, and cancer pathogenesis display considerable similarities. Maintaining redox homeostasis, efficient signal transduction, and mitochondrial metabolism is essential for genome integrity and for preventing progression to cellular senescence or tumorigenesis. NAD+ is a central signaling molecule involved in these and other cellular processes implicated in age-related diseases and cancer. Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 171 publications
0
32
0
7
Order By: Relevance
“…In this review, we will focus on the compartmentalized regulation of NAD + biosynthesis and metabolism in cancer development and progression, as well as on currently available small molecules targeting NAD + and its associated biomolecules for cancer treatment. For a comprehensive understanding of the NAD + metabolome in tumorigenesis, we refer readers to several excellent reviews recently published that cover the topic extensively (Demarest et al, 2019;Sharif et al, 2019;Yaku, Okabe, Hikosaka, & Nakagawa, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we will focus on the compartmentalized regulation of NAD + biosynthesis and metabolism in cancer development and progression, as well as on currently available small molecules targeting NAD + and its associated biomolecules for cancer treatment. For a comprehensive understanding of the NAD + metabolome in tumorigenesis, we refer readers to several excellent reviews recently published that cover the topic extensively (Demarest et al, 2019;Sharif et al, 2019;Yaku, Okabe, Hikosaka, & Nakagawa, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has become apparent that altered NAD + metabolism is correlated with several metabolic disorders and diseases, and therapeutic approaches by modulation of the NAD + biosynthetic and consuming pathways using NAD + precursors or chemical inhibitors are being actively explored [134][135][136][137]. Changes in NAD + metabolism affect many cellular processes either through redox metabolism or activities of NAD + -consuming enzymes.…”
Section: Nad + and Diseasesmentioning
confidence: 99%
“…The mechanisms of these pyridine nucleotides to act as essential cofactors in redox reactions, or substrates in ribosyl transfer reactions, have been recently reviewed in detail [ 21 ]. Moreover, in addition to these regulatory functions, recent work has shown that NAD + and its metabolites also regulate the activity of ion channels, including the Slo K + channels, voltage-gated potassium channels and sodium channels, ATP-regulated K + channels, and some specific types of calcium channels [ 8 ].…”
Section: Introductionmentioning
confidence: 99%